Access charges, vertical separation, and lobbying - Toshihiro Matsumura; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2011)
We examine how vertical separation affects the lobbying activities for the access charge of essential facilities. First, when investigating a model where the number of new entrants is fixed, we find that vertical separation either increases or decreases the access charge, and that this depends on the relative efficiency between the incumbent and the new entrants, and the number of entrants. Second, when investigating a freeentry market, we find that vertical separation always reduces the access charge in such a market. The vertically integrated firm has a stronger incentive to lobby in this market because a higher access charge reduces the number of competitors.
Keywords: L51; L13; 330; network industry; access charge; manipulation of accounting; regulation; Netzregulierung; Vertikale Integration; Regulierung; Unvollkommener Markt; Regulierungstheorie